2023
DOI: 10.1007/s42832-022-0159-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial enzymatic stoichiometry and the acquisition of C, N, and P in soils under different land-use types in Brazilian semiarid

Abstract: The enzymatic stoichiometry varied between land-use in both soil depth.• The values of C-and N-acquiring enzymes were higher at 0−5 cm depth.• Soils under different land-use types in the Brazilian semiarid are P-limited. This study hypothesized that different land-use affect the microbial enzymatic stoichiometry and C-, N-, and P-acquisition in Brazilian semiarid soils. Thus, the enzymes β-glucosidase (C-acquiring enzyme), urease (N-acquiring enzyme), and acid phosphatase (P-acquiring enzyme) were assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In general, the values of C-, N-, and P-acquiring enzymes were higher in native and restored soils, and it could be related to the permanent presence of vegetation in native (e.g., herbaceous plants, stunted trees, and bushes) and restored (grazing exclusion with secondary vegetation) soils . Previous studies have reported that the presence of plants contributed to higher values of C-, N-, and P-acquiring enzymes (Piotrowska-Długosz et al, 2022;Medeiros et al, 2023). In contrast, degraded soils, which does not present plants neither litter, presented the lowest values of C-, N-, and P-acquiring enzymes.…”
Section: Soil Microorganisms Are Essential In Soil Ecosystem Function...mentioning
confidence: 81%
“…In general, the values of C-, N-, and P-acquiring enzymes were higher in native and restored soils, and it could be related to the permanent presence of vegetation in native (e.g., herbaceous plants, stunted trees, and bushes) and restored (grazing exclusion with secondary vegetation) soils . Previous studies have reported that the presence of plants contributed to higher values of C-, N-, and P-acquiring enzymes (Piotrowska-Długosz et al, 2022;Medeiros et al, 2023). In contrast, degraded soils, which does not present plants neither litter, presented the lowest values of C-, N-, and P-acquiring enzymes.…”
Section: Soil Microorganisms Are Essential In Soil Ecosystem Function...mentioning
confidence: 81%